Landasan Aksiologis bagi Sistem Pendidikan di Masa Depan - Jirzanah Jirzanah (Fakultas Filsafat, Universitas Gadjah Mada Yogyakarta, 1999)
Education always exists in the center of cultural concrete circumstances. It begins with studying from the past, creates the recent concrete circumstances and consciously arranges the future. Indonesia has had a value system based on the Indonesia culture itself, so that in the process of transformation, that value system will become the spirit of Indonesian people in the future. Accordingly, in this research, the critical evaluations about the national educational cores and objectives as formulated in Undang-undang No. 2 Tahun 1989 (Ordinance No. 2 yer 1989) is arranged in order to know their matching with the development of education in the future.This research is a bibliographical study. Its data were collected from some bibliographical sources. The books investigated were those which studied the national education and Undang-undang No. 2 Tahun 1989 (Ordinance No. 2 year 1989) about National Educational System. Bibliographies on Philosophy of Culture, Pancasila (the Five Principles). Antrophology and Value were used as materials for arranging the analysis of the axiological foundation for the National Education System. The collected data were analyzed by using hermenutical method. The elements of hermeneutical method are description, interpretation, and reflection. Descriptive method is used to find the corer or materials and objectives of the National Education System. The interpretative method is used to find the foundation of value, culture, and axiology of the National Educational System. Lastly, the reflective method is used to critically arrange the axilogical foundation for developing future global educational system.The main result of this research showed that the axiological foundation of National Education System was the ability of rationality having characteristic of freedom and creativity inspired by the value of Pancasila. The National Education System as the actualization of Indonesia value and culture was on open system, that it would always be relevant with the development in both national and global scopes. The National Educational System has given the foundation and framework in the process of actualization for keeping its relevance with the exchange of time. National curriculm have determined the divisions of lesson subject matter for keeping the national sight to grow in order the leaners know the probelms of Indonesia national struggle. Morever, the national curriculum has also determined the determined of divisions of lesson for keeping the freedom and creativity to grow, so that the rational freedom and creativity will always be inspired by the value of Indonesian nationality, that is Pancasila.